Biodegradable double-network GelMA-ACNM hydrogel microneedles for transdermal drug delivery - Lin, Wensheng; Lin, Shixian; Zhou, Xingwu; Yang, Fanwen; Lin, Zishan; Li, Shiqing; Zhang, Haoyuan; Ouyang, Yuehan; Zhu, Jieying; Sun, Wei; Huang, Dequn; Liao, Baojian; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
As a minimally invasive drug delivery platform, microneedles (MNs) overcome many drawbacks of the conventional transdermal drug delivery systems, therefore are favorable in biomedical applications. MNs with a combined burst and sustained release profile and maintained therapeutic molecular bioactivity could further broaden its applications as therapeutics. Here, we developed a double-network MNs (DN MNs) based on gelatin methacrylate and acellular neural matrix (GelMA-ACNM). ACNM could function as an early drug release matrix, whereas the addition of GelMA facilitates sustained drug release. In particular, the DN MNs comprising GelMA-ACNM hydrogel has distinctive biological features in maintaining drug activity to meet the needs of application in treating different diseases. In this study, we prepared the DN MNs and evaluated its morphology, mechanical properties, drug release properties and biocompatibility, which shows great potential for delivery of therapeutic molecules that needs different release profiles in transdermal treatment.